Sprache des Rechts - Vermitteln, Verstehen, Verwechseln = The language of law - communication, understanding and misunderstanding - Klein, Wolfgang (Zeitschrift für Literaturwissenschaft und Linguistik, 2017)
This paper describes a large interdisciplinary project on the language of legal texts presently undertaken at the Berlin-Brandenburgischen Akademie der Wissenschaften. Its focus is on comprehensibility of legal texts and on variation in their understanding across different groups of addressees. In two ways, it differs from most research in this important but difficult area. First, it brings together legal and linguistic experts, and second, it is strictly empirical. A first subproject deals with various attempts to reformule and to rephrase the Bürgerliche Gesetzbuch and other laws related to it, such as the Zivilgesetzbuch der DDR. A second subproject is devoted to specific linguistic phenomena which often give rise to differences and problems of interpretation, such as scope, anaphoricity or the meaning of modal constructions. A third subproject addresses two issues: the requirement of ›transparency‹ in insurance contracts and similar texts and the legal protection of registered trade marks.
Das Projekt der Berlin-Brandenburgischen Akademie der Wissenschaften geht auf Überlegungen von Rainer Dietrich, Wolfgang Klein,Wolf-Hagen Krauth, Ingeborg Lasser, Dieter Simon, Christine Windbichler zurück; eine Reihe weiterer Mitglieder der Akademie hat sich durch Anregungen und Kritik beteiligt
Gesehen am 23.12.2020